PENERAPAN METODE PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SD NEGERI 001 BINAMANG - Zainal Abidin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
Based on the results of observations of students in grade VI SD Negeri 001 Binamang known that during theprocess of science learning took place in the classroom seen that there are still many students who are lessconcentrated in learning, while doing the task of many students who see his friend's work, and student learningmotivation in the learning process IPA is not optimal so that result of learning result of IPA obtained by studentstill low. Only 55.6% achieved KKM in science subjects. The purpose of this study is to know that the applicationof thinking pair share learning method can improve science learning outcomes in grade 6 students of SD Negeri001 Binamang. This research was conducted in the 6th grade of SD Negeri 001 Binamang in the odd semester ofthe 2016/2017 learning year. This research started from September 2016 until October 2016. The subject of thisclass action research was conducted on grade 6 students of SD Negeri 001 Binamang. Number of students 18students consisting of 6 female students and 12 male students. This research is a classroom action research withthe application of thinking pair share learning method. This study consists of two cycles and each cycle consistsof four stages of planning, implementation, observation and reflection. The results of this classroom actionresearch is the application of thinking pair share learning method can improve the learning outcomes of sciencestudents of grade VI SD Negeri 001 Binamang academic year 2016/2017. Learning outcomes before PTK is 72.0with less category. The result of learning cycle I meeting 1 is 75.0 with enough category and at meeting 2 is 77.8with enough category. The result of learning cycle II meeting 3 is 80.0 with good category and at meeting 4 is82.2 with good category.